Utility of Urine Reagent Strips in CSF Analysis as An Aid to Rapid Diagnosis of Meningitis - R, Abhirami Ganesh; H, Prabhu M (Annals of Pathology and Laboratory Medicine, 2020)
Background: Bacterial Meningitis is a medical emergency and timely intervention has an implication on the prognosis and outcome. Examination of the CSF for leucocytes, glucose and proteins are the cornerstones in the diagnosis of meningitis in general and to arrive at the cause. Hence, this study is done to evaluate the usefulness of urinary reagent strip for rapid diagnosis of meningitis. Methods: This is a prospective single blinded study on 100 CSF samples subjected to index test (Urine reagent strip test-Dirui H10) and definitive test comprised of CSF microscopy and biochemical analysis for proteins and sugar. The diagnostic accuracy of each index test at different cut off levels tabulated in the form of sensitivity, specificity, PPV and NPV. Result: The sensitivity and specificity for leukocytes by the strip method for â‰¥15 cells/cumm were 92% and 98.66%, and for protein levels >30 mg/dl were 84.33% and 94.11% respectively. The test showed high specificity (100%) but less sensitivity for glucose <50mg/dl. It was observed that the accuracy of the tests increased with increase in the values of cell counts and proteins and decrease in sugar reaching 100% accuracy for higher cut-offs. Conclusion: Urine reagent strip can be utilized for the rapid analysis of CSF in both rural areas as well as in centres where the facility is available as it reduces turnaround time.